GEOLOGI, ALTERASI HIDROTERMAL, DAN MINERALISASI DAERAH ONTO DAN SEKITARNYA, KECAMATAN HUâU, KABUPATEN DOMPU, PROVINSI NUSA TENGGARA BARAT - Febriansyah, Alif; Aribowo, Yoga; Widiarso, Dian Agus (Geological Engineering E-Journal, 2014)
The use of metallic minerals as raw materials is increasing. Therefore, Indonesia needs to improve metallic mineral reserves for the needs of the country and internationally to explore maximally. This can be done because some parts of Indonesia has huge reserves of metallic minerals.. This research purposed to learn about geological condition of research area involve morphology, lithology, and structure geology, determine alteration zone, and learn distribution of Copper (Cu) that contained in research area.Methodology used in this research is survey method and analysis method. Survey methos by doing surface geological mapping. Analytical method by doing petrology analyisis, petrography analysis, mineragraphy analysis, ASD analysis (Analytical Spectral Device) and sturcture geology analysis.Geomorphology of Onto and the surrounding divided into two units are volcanic very steep hill unit and volcanic steep hill unit. Lithology of research area from olderÂ  to younger are tuff, volcanic breccia and breached by porphyrytic andesite. Structure geology in research area in the form of alignment pattern by Dem Map (Digital Elevation Model) in period I direction of structure is west-east and northwest-southeast, whereas in period III direction is north-south. The alteration zone of research area are divided into advanced argillic zone associated with dickite, alunite, and kaolinite minerals; argllic zone associated with kaolinite, palygorskite, and siderite minerals; and intermediet argillic associated with palygorskite and Chlorite minerals. Mineralization of research area is in the form of stockwork and disseminated whick mineralized by pyrite and chalcopyrite as ore mineral. Type of mineralization deposition in research area is Porphyry depoosition type. The value levels of Copper in research area are potential with 1132,79 ppm in tuff unit STA. 33, STA. 35 with value levels of copper is 130,01 ppm, STA. 55 is 390,37 ppm, STA. 56 is 499,9 ppm and STA. 73 is 288,95 ppm.